KOMUNIKASI INTERPERSONAL KAUM LESBIAN DALAM BERINTERAKSI SOSIAL - Dekantari, Renanda Feby (JURNAL KOMUNITAS, 2018)
Lesbian is a social phenomenon that cannot be denied. The existence of lesbian is recognized as a reality in the society and raise various reaction from the surrounding area. The denial from the surroundingand wider area made the lesbian feel afraid, doubtful, and even ashamed toshow their true sexual identity. Thus became a persecutor to communicatewith the society. The communication involved between the lesbian and thesociety is not easy, it needs process that the communication can be doneand in the end the lesbian existence can be admitted or accepted by thesurrounding area in such way that create the mutual understandingcommunication.To get the admission of their existence as a lesbian in thesurrounding society, the lesbian have to get involved in personalcommunication process. When the lesbian stated their selves and interactthrough interpersonal communication, certainly there is a distinctivepressure in deciding what will be stated and what should be under the rose.The research concerning lesbian interpersonal communication inâ€œBelokâ€ community at Solo City is a descriptive qualitative research. Theprocess in conducting this research emphasized in qualitative research. Inorder to be done further, this research was focused on the symbolicinteraction done by the lesbian about their selves and then observes howthe lesbian community interacts with the surrounding society which isformed into their interpersonal communication using socio-cultural method